1998
DOI: 10.1038/33345
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of mouse telomerase in highly proliferative organs

Abstract: We have investigated the role of the enzyme telomerase in highly proliferative organs in successive generations of mice lacking telomerase RNA. Late-generation animals exhibited defective spermatogenesis, with increased programmed cell death (apoptosis) and decreased proliferation in the testis. The proliferative capacity of haematopoietic cells in the bone marrow and spleen was also compromised. These progressively adverse effects coincided with substantial erosion of telomeres (the termini of eukaryotic chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

62
994
4
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,183 publications
(1,064 citation statements)
references
References 38 publications
62
994
4
4
Order By: Relevance
“…Specifically, senescent cells and/or molecular markers of the senescent phenotype have been reported to increase in some aging tissues [40,41,[64][65][66][67][68][69], and are linked to some age-associated tissue pathologies, such as osteoarthritis, atherosclerosis and liver cirrhosis [70][71][72]. Moreover, manipulation of the cell signals that initiate senescence, such as telomere length and expression of the proliferation inhibitor p16INK4a [66][67][68]70,[73][74][75][76][77][78][79][80], can modulate some aspects of organismal aging [70][71][72]. In addition to a likely role in tissue aging, cellular senescence is also a well-established tumor suppression process, by virtue of its ability to arrest proliferation and neoplastic progression of cells harboring oncogenic lesions [81][82][83][84][85][86][87].…”
Section: Cellular Senescence Is Associated With Redistribution Of Hetmentioning
confidence: 99%
“…Specifically, senescent cells and/or molecular markers of the senescent phenotype have been reported to increase in some aging tissues [40,41,[64][65][66][67][68][69], and are linked to some age-associated tissue pathologies, such as osteoarthritis, atherosclerosis and liver cirrhosis [70][71][72]. Moreover, manipulation of the cell signals that initiate senescence, such as telomere length and expression of the proliferation inhibitor p16INK4a [66][67][68]70,[73][74][75][76][77][78][79][80], can modulate some aspects of organismal aging [70][71][72]. In addition to a likely role in tissue aging, cellular senescence is also a well-established tumor suppression process, by virtue of its ability to arrest proliferation and neoplastic progression of cells harboring oncogenic lesions [81][82][83][84][85][86][87].…”
Section: Cellular Senescence Is Associated With Redistribution Of Hetmentioning
confidence: 99%
“…Expression of hTERT stimulates cell proliferation toward immortality [12][13][14][15][16] and contributes to tumor formation [17,18]. In contrast, inhibition of telomerase results in erosion of telomeres, compromise of growth capacity and apoptosis of highly proliferative cells [19][20][21][22][23][24]. Thus, hTERT is essentially a key element in telomerase activation, telomere maintenance and tumor development, and is proposed as a promising target for anticancer therapy.…”
Section: Telomeres and Telomerasementioning
confidence: 99%
“…Its precise role in normal cells has not yet been fully explored. Telomerase maintenance of telomeres has been proposed to play a critical role in preserving genomic stability and long term viability of highly proliferative organ systems (Lee et al, 1998). Recent works have shown that after successive generation mice genetically de®cient for the telomerase RNA (mTER null mice) present defects in germ cell growth, uterine and intestinal villus atrophy, impaired lymphocyte mitogenesis, diminished hematopoietic reserves, ulcerative dermatitis and alteration of nervous system development (Blasco et al, 1997;Herrera et al, 1999a,b).…”
Section: Introductionmentioning
confidence: 99%